Screening for small subunit of ADP-glucose pyrophosporylase (AGPase) from sago palm using custom designed oligonucleotides - Rosni, Bt. Ismail. (Universiti Malaysia Sarawak (UNIMAS), 2005)
The first part of this study involved an attempt to isolate the small subunit of ADPglucose pyrophosphorylase (AGPase). Two primers were constructed based on previous published conserved amino acid sequences of the small subunit of AGPase. Out of these, only one set of primer (ha2AGP), manage to produce a desired PCR product. PCR amplification using this primer gave 3 bands products with the sizes range from 250bp to 500bp. When transformed into E. coli JMI 09, few white colonies were observed on the LB agar plate. The plasmid was successfully isolated but PCR amplification of the isolated plasmid failed to amplify the inserted DNA fragments. Restriction enzyme digestion with EcoRI to the isolated plasmid also did not give any desired results. The second part of the study was to obtain the protein concentration in young and photosynthetic leaves of sago palm. Protein extraction was successfully accomplished. Protein band was detected when run under nondenaturing PAGE condition and stained using Coomassie blue.